2014
DOI: 10.1016/j.jcrysgro.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanostructures formation in porous Si/SiO2 matrix

Abstract: Self-organized silver nanostructures were grown in porous Si/SiO 2 matrix fabricated by ion track technology. The different silver nanostructures with shapes like "sunflowers", "azalea" or "corn" were realized by applying wet-chemical electroless deposition. We show that reproducible self-organized silver "sunflower" like nanostructures provide a high enhanced Raman signal of Nile blue dye molecules. Signal enhancement for a few or even just a single silver "sunflower" is demonstrated by analyzing the surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…The self-assembled silver nanostructures grew in template by ion track technology, and the template coated with active sites could support the formation of Ag nanoparticles. The self-assembled Ag dendrites formed in porous Si/SiO 2 matrix and SiO 2 nanoparticles didn't need any additional reagents during the reaction [55]. Factors that affect the Ag nanostructures formation in the templates include the structure of the template, presence of surface active agents, and the reaction conditions.…”
Section: Ag Dendrites Fabrication Via Template Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assembled silver nanostructures grew in template by ion track technology, and the template coated with active sites could support the formation of Ag nanoparticles. The self-assembled Ag dendrites formed in porous Si/SiO 2 matrix and SiO 2 nanoparticles didn't need any additional reagents during the reaction [55]. Factors that affect the Ag nanostructures formation in the templates include the structure of the template, presence of surface active agents, and the reaction conditions.…”
Section: Ag Dendrites Fabrication Via Template Methodsmentioning
confidence: 99%
“…Fu et al [65] fabricated Ag dendrites/AgCl hybrid thin film on ITO electrode with electrolyte consisting of silver-ammonia [Ag(NH 3 ) 2 OH] and certain amount of hexadecyl trimethyl ammonium chloride (CTAC). Investigation revealed that the Ag dendrites consisted of a long central stem with side branches emerge at about 55 and when using higher content of CTAC, the growth of Ag dendrites was suppressed while the numbers of polyhedral AgCl dramatically increased. Polyethylene glycol (PEG) [66], mixed surfactants of cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulphate [67] and sodium dodecanesulphonate (SDS) [68] are also mixed with AgNO 3 solution for fabrication of dendritic silver nanocrystals.…”
Section: Ag Dendrites Fabrication Via Electrochemical Methodsmentioning
confidence: 99%
“…) is similar to that of Ag nanosponges prepared by reduction of silver nitrate in a multicomponent system and by a subsequent thermal fusion during shaking at 60 °C as well as to Ag‐quantum dots sponge‐like nanocomposites . Concerning the employment of the nanostructures for the purposes of SERS spectroscopy, the major difference between the last mentioned Ag nanosponges, as well as the other types of recently prepared Ag nanostructures, and the macroscopic nanosponge Ag aggregates reported in this paper is that the analyte has been already incorporated into their fractal building blocks. Therefore, while the former Ag nanostructures represent substrates for SERS, the latter represents a SERS active system in which an analyte is already localized by a simple addition of its aqueous solution (of varying concentrations) into the parent HA‐Ag NP hydrosol/HCl system.…”
Section: Resultsmentioning
confidence: 99%
“…A simple method based on the application of a porous matrix for the controlled and localized formation of complex shape plasmonic metal nanostructures has been proposed in our previous publications [23][24][25]. It was shown that the morphology of aggregated structures of copper and silver can be controlled over the large silicon surfaces via galvanic replacement.…”
Section: Introductionmentioning
confidence: 99%